Full‐color multi‐plane optical see‐through head‐mounted display for augmented reality applications. Issue 12 (15th October 2018) - Liu, Shuxin; Li, Yan; Zhou, Pengcheng; Chen, Quanming; Li, Sida; Liu, Yueda; Wang, Yunfeng; Su, Yikai
Abstract: Based on fast‐response polymer‐stabilized liquid crystal scattering shutters, we designed a full‐color multi‐plane optical see‐through head‐mounted display for augmented reality applications. Red, green, and blue light‐emitting diodes (LEDs) are used to illuminate a digital micromirror device in time sequence to create a full‐color 3D scene. A quasi‐collimated image projection source, with a large depth of focus, was designed, in order to ensure sharp pictures projected on different polymer‐stabilized liquid crystal films at different depth. Our system provides high‐quality full‐color images with correct depth information and thus solves the accommodation–vergence conflict problem. A proof‐of‐concept binocular full‐color two‐plane optical see‐through head‐mounted display prototype is demonstrated. Abstract : In this paper, we design a full‐color multi‐plane optical see‐through head‐mounted display, by using three light‐emitting diodes (red, green, and blue), a digital micromirror device, and fast response polymer‐stabilized liquid crystal scattering shutters. Our system provides high‐quality full‐color images with correct depth information and thus solves the accommodation–vergence conflict problem.